The Struggle of the Lesotho Evangelical Church in Southern Africa (LECSA)/Paris Evangelical Missionary Society (PEMS) in Meadowlands, Soweto, in becoming a missional ecclesia in a local context - Kgatla, Selaelo T. (University of Pretoria, 2016)
Dissertation (MA)--University of Pretoria, 2016.